(untitled) (Eurasian Medical Research Periodical, 2023)
Objectives of current research was to determine the rate of anti-obesity medications use among Basrah university students (Bab Al-Zubair Colleges) and to evaluate students’ knowledge about these medications. One hundred students from different four Bab AlZubair colleges were interviewed using questionnaires established for the study. The study revealed that approximately half of the university students (54 %) were consumed anti-obesity medications. (48%) of them within normal weight, (33%) were overweight, and while (19%) obese. Most of them never partake in exercise (61%). 67% of the consumers have information about medications and their adverse effects. The physicians and social media are the main sources of information (44%, 33%) respectively. (48%) of them believed that anti-obesity medications can be used safely. (39%) of them were self-administrated without prescription, and (44%) prescribed by physician. Approximately one-third of the consumers (30%) experienced adverse effects while using medications. Diarrheaand oily spotting are the main adverse effects among them (30 %). (37 %) ofstudents prescribed anti-obesity drugs to others. There is significant relationshipbetween gender, BMI, and anti-obesity medications consumers (p-value ≤0.05).